The war of words : how America's GI journalists battled censorship and propaganda to help win World War II - Manning, Molly Guptill, 1980- (Blackstone Publishing, 2023)
"At a time when civilian periodicals faced strict censorship, US Army Chief of Staff George Marshall won the support of President Franklin Delano Roosevelt to create an expansive troop-newspaper program. Both Marshall and FDR recognized that there was a second struggle taking place outside the battlefields of World War II--the war of words. While Hitler inundated the globe with propaganda, morale across the US Army dwindled. As the Axis blurred the lines between truth and fiction, the best defense was for American troops to bring the truth into focus by writing it down and disseminating it themselves. By war's end, over 4,600 unique GI publications had been printed around the world. In newsprint, troops made sense of their hardships, losses, and reasons for fighting. These newspapers--by and for the troops--became the heart and soul of a unit. From Normandy to the shores of Japan, American soldiers exercised a level of free speech the military had never known nor would again. It was an extraordinary chapter in American democracy and military history. In the war for "four freedoms," it was remarkably fitting that troops fought not only with guns but with their pens. This stunning volume includes fourteen pages of photographs and illustrations"--